Music interventions for dementia and depression in elderly care (MIDDEL): The Australian part of an international cluster randomised controlled trial. (December 2021) - Baker, Felicity; Lee, Young‐Eun C; Sousa, Tanara; Stretton‐Smith, Phoebe; Clark, Imogen; Sveinsdottir, Vigdis; Geretsegger, Monika; Gold, Christian
Abstract: Background: Dementia and depression are highly prevalent, comorbid conditions in older adults residing in care homes and are associated with individual distress and associated challenges for care staff. Music‐based interventions are widely used and potentially effective nonpharmacological interventions, due to the relative preservation of the ability of people with dementia to respond to music even with disease progression. However, there is a lack of large‐scale studies evaluating the effectiveness of music‐based interventions in dementia care. Music Interventions for Dementia and Depression in the Elderly (MIDDEL) is the first large‐scale international cluster‐randomised controlled trial to investigate the effectiveness of small group music therapy (GMT), recreational choir singing (RCS) and their combination on levels of depression in residents with dementia. The trial is currently being conducted across six countries, and this presentation will outline the study outcomes from the Australian arm of the trial. Method: Between June 2018 and November 2019, 20 care home units were randomised to music interventions (GMT, RCS, GMT and RCS) or standard care delivered over 6 months. The primary outcome was level of depression as measured by the Montgomery‐Asberg Depression Rating Scale (MADRS). Secondary outcomes included neuropsychiatric symptoms, quality of life, care staff burden and adverse events collected at baseline, 3‐months, 6‐months and 12‐months post‐randomisation. Outcomes were analysed as intention‐to‐treat, per‐protocol, and with exploratory predictor analyses. Results: 318 participants (215 female; 103 male) aged 65 years or more with diagnoses of dementia and at least mild depressive symptoms (as defined by score of 8 or above on MADRS) residing in care homes were recruited. In addition, 131 care staff (108 female; 23 male) answered questions regarding perceived care burden to search for potential ripple effects of the music interventions. We will present the main findings of the study including the predictive effects of clinical characteristics on efficacy. Conclusion: The presentation will include discussion of contextual factors and conditions that support efficacy, and clinical implications for safety and quality of life for people with dementia living in care homes.